Dziad i baba - Kraszewski, Jozef Ignacy, 1812-1887.; Gaudasinska, Elzbieta (Warszawa : Nasza Ksiegarnia, 1991)
A story in verse for pre-school and elementary school children.
Keywords: Children's poetry, Polish